Metabolite Variation of Peanut Hulls (Arachis hypogaea L.) from Three Locations of Lombok Island on the Basis of GC-MS Analysis - Surya Hadi; Dina Asnawati; Baiq Mariana; Hijriati Sholehah; Andhina Rizkya Satriani; Seto Priyambodo (Chemistry Department, The University of Brawijaya, 2017)
This article is a part of studies to investigate the potential of natural products from Lombok Island for antidiabetic agents. This study was directed to learn the metabolite variations of peanut hulls collected from three different locations in Lombok Island. The hull samples were extracted in methanol, followed by partition process into three fractions using three solvents with varied polarities (dichloromethane, hexane and acetone). The fractions were then separated and identified for their chemical composition by using GC-MS instrument. Metabolite variations of three extracts showed that the antidiabetic compounds stigmast-5-en-3-ol and oleic acid were found in all three locations with different percentages of abundance. Another antidiabetic compound, linoleic acid, was only identified in peanut hulls from the village of Pringga Jurang (PJ). Besides the antidiabetic compounds, there were other major compounds with known biological activities discussed to find other uses of the hulls.